Cervical cancer screening among English- and Spanish-speaking Hispanic women in an urban safety net health system, 2015-2020 - Trisha L. Amboree; Susan Lackey Parker; Shaun Bulsara; Matthew L. Anderson; Kathleen M. Schmeler; Elizabeth Y. Chiao; Jane R. Montealegre (BMC, 2023)
Abstract Background The Hispanic population is heterogeneous with differences in health behaviors across subgroups by nativity and preferred language. We evaluated cervical cancer screening adherence among English- and Spanish-speaking Hispanic patients receiving care at a safety net health system. Methods Electronic health records were used to identify 46,094 women aged 30-65. Up to date (UTD) screening was defined based on date of last Pap test, human papillomavirus (HPV) test, or Pap/HPV co-test. Results Overall, 81.5% of 31,297 Hispanic women were UTD. English-speaking Hispanic women had a lower prevalence of being UTD when compared to Spanish-speaking Hispanic women (aPR: 0.94, 95% CI: 0.93 - 0.96). Further, those with indigent healthcare plans had a higher prevalence of being UTD when compared to those with private insurance (aPR: 1.10, 95% CI: 1.09 - 1.12), while all other health insurance plans were associated with lower UTD screening when compared to private insurance. Conclusions These findings suggest screening differences within the Hispanic population, highlighting the need for disaggregated research assessing heterogeneity within racial/ethnic groups, specifically among Hispanic populations.